Construction of nanomaterials as contrast agents or probes for glioma imaging - Wei Zhao; Xiangrong Yu; Shaojun Peng; Yu Luo; Jingchao Li; Ligong Lu (Journal of Nanobiotechnology, 2021)
Abstract Malignant glioma remains incurable largely due to the aggressive and infiltrative nature, as well as the existence of blood–brain-barrier (BBB). Precise diagnosis of glioma, which aims to accurately delineate the tumor boundary for guiding surgical resection and provide reliable feedback of the therapeutic outcomes, is the critical step for successful treatment. Numerous imaging modalities have been developed for the efficient diagnosis of tumors from structural or functional aspects. However, the presence of BBB largely hampers the entrance of contrast agents (Cas) or probes into the brain, rendering the imaging performance highly compromised. The development of nanomaterials provides promising strategies for constructing nano-sized Cas or probes for accurate imaging of glioma owing to the BBB crossing ability and other unique advantages of nanomaterials, such as high loading capacity and stimuli-responsive properties. In this review, the recent progress of nanomaterials applied in single modal imaging modality and multimodal imaging for a comprehensive diagnosis is thoroughly summarized. Finally, the prospects and challenges are offered with the hope for its better development.